دقة الإحساس الحركي للطالبات الممارسات للرياضة في المدرسة الثانوية "دراسة مقارنة" - بركات, نوري (Latakia University Journal -Medical Sciences Series, 2019)
تعد دقة الإحساس الحركي أحد أهم مقومات تكيف وتوافق الفرد مع البيئة ومتغيراتها والممارسة الرياضية أحد أهم العوامل الأساسية التي تنمي وتطور هذه الصفة العقلية, وعليه أجريت هذه الدراسة المقارنة على عينة مكونة من 64 طالبة في الصف الأول الثانوي والثاني الثانوي /32/ طالبة ممارسة للرياضة و/32/ طالبة غير ممارسة لها. وقد أظهرت الدراسة أن هناك فروقاً في قيمة الإحساس الحركي بين الممارسات وغير الممارسات للرياضة وأن الممارسات لها أفضل في دقة الإحساس الحركي وأن الممارسة الرياضية ذات تأثير إيجابي في هذه الصفة وأنها تعمل على نموها وتطويرها, لذا أوصى الباحث بضرورة الاهتمام بالممارسة الرياضية في المدارس كنشاط منظم ونشاط حر يتيح الفرص لمعظم الطالبات الاستفادة منها. Accuracy of kinetic sense is considered one of the most important constituents of the individual's adaptation and harmony with the environment and its variations. Sporting practice is one of the important basic factors which develops and promotes this mental attribute. Thereon this comparative study was carried out on a sample consisted of 64 female students in the first and second Secondary Class. 32 female students were sport practising and 32 female students were non-practising of sport. The study has shown that there are differences in the value of the accuracy of the kinetic sense among the accuracy, and that sport practice has positive effect on this attribute and that it works for its development and promotion. Therefore, the researcher has recommended the necessity of giving caring to sport practice at schools as organized activity and free activity that allows the chance to benefit from which the majority of the students.